Analysis of Management of Traditional Market Retribution in Increasing Paddy in Pare Village - Pare District, Kediri Regency - Eko Prasetyo; Bella Paradita; Bella Arum Kristanti (Formosa Journal of Applied Sciences, 2023)
Retribution is a source of Regional Original Income (PAD) which has a significant contribution to regional development if the source of income can be managed properly. In the context of implementing good management, one of the efforts that can be made is to implement records that support and are in accordance with the applicable rules in good and appropriate regulations so that all forms of fraud and fraud in the collection and management can be anticipated beforehand. This study aims to determine the management of traditional market fees in increasing local revenue. The research method used is qualitative with a descriptive approach. From the results of research conducted for collection and management procedures are in accordance with the regulations in force in the local government. To increase income, researchers suggest socializing the purpose of collecting and using e-levies.